A note on money and credit money: an interpretation of Marx's value theory - Araujo, Renan Ferreira de (2021)
The aim of this paper is to reconstruct the genetic development of money in Marx’s value theory from a value-form approach. In particular, we argue that Marx's theory of money is not limited to the conception of money as a specific commodity, such as gold. We highlight that, methodologically, commodity money is only a stage in the systematic development of money, which points to credit money within the process of capital valorization as its most finished form. Therefore, this paper aims to contribute to the rich Marxist literature on the understanding of money in contemporary capitalism by bringing forward the compatibility of Marx's theory of money for understanding the contemporary forms assumed by money.